Sexual Assault and Sexual Harassment in the U.S. Military Volume 1. Design of the 2014 RAND Military Workplace Study - Morral, Andrew R. (RAND Corporation, 2014)
The Department of Defense Sexual Assault Prevention and Response Office asked the RAND Corporation to conduct an independent assessment of sexual assault and sexual harassment in the US military. This volume documents the methodology used in the resulting RAND Military Workplace Study, which invited close to 560,000 service members to participate in a survey fielded in August and September of 2014.